Islamic Legal Pluralism and Contemporary Educational Implementation Based on Maqasid al-Syariah - Erizal Erizal; Metriadi Metriadi; Zidni Ilman Nafian; Riki Saputra; Sukmareni Sukmareni (International Journal of Multidisciplinary Research of Higher Education, 2026)
Pluralism has emerged as a strategic issue in multicultural societies and continues to be debated within the discourse of Islamic law and contemporary education. On the one hand, pluralism is perceived as an essential instrument for building peaceful and inclusive social life, while on the other hand, it is often associated with religious relativism. This study aims to analyze the concept of pluralism from the perspective of Islamic law, identify its normative foundations in the Qur’an, Sunnah, and classical scholarly thought, and reconstruct its implementation model in contemporary education. Employing a qualitative method with normative, philosophical, and conceptual approaches, the research applies Miles and Huberman’s data analysis technique, consisting of data reduction, data display, and conclusion drawing/verification. Primary sources include the Qur’an, hadith, and classical Islamic legal literature, while secondary sources comprise reputable journal articles and academic books published between 2020 and 2026. The findings reveal that pluralism in Islamic law is grounded in the principles of ta‘āruf, tasāmuḥ, al-‘adālah, al-musāwah, and al-ta‘āwun, all directed toward achieving social welfare. The maqāṣid al-syarī‘ah analysis demonstrates the relevance of pluralism to the protection of religion, life, intellect, lineage, and property. The study offers the novelty of an Islamic Legal Pluralism-Based Education model, integrating Islamic legal principles, maqāṣid al-syarī‘ah, and multicultural education into a systematic conceptual framework to foster inclusive, moderate, and responsive Islamic education in the plural society of the twenty-first century.